GENERAL AN OVERVIEW AT HAYDN, MOZART AND BEETHOVEN SONATAS - Barış TOPTAŞ (Fırat University, 2019)
International Classical Music (classical music) passed through many stages until today. These stages were defined as the period in music history . These periods are respectively, Medieval Period, Renaissance Period (1456-1600), Classical period (1600-1750), Romantic Period (1750-1830), modern (contemporary) Period (1830-1900) and the present-day (1900 - ....).The classicial period, history in golden letters in the names of prints known as the Vienna Classics three composers; Haydn, Mozart and Beethoven, shed light on many innovations in their periods and have preserved their place at the height of today's music. From one of these composers have composed works for different instruments in many forms and types. All these works have been important building blocks of the classical period. Sonata form is well developed in this period. Almost written sonatas for all instruments. Especially a lot of works composed in sonata form developed performers as well as the technical limits of the instruments. Among these works, piano sonatas play an important role. In this study, Haydn'ın 52 piano sonatas, 19 piano sonatas of Mozart and Beethoven 32 piano sonatas examined in terms of tonal structures. Used piano sonatas tones (Tone Sonata), the intermediate section in conjunction with the main tone shades and degrees of them were examined. Haydn's piano sonatas using intermediate section crossing the 65.4% percent compared to the 1st degrees, Mozart's piano sonatas using tone intermediate section of 47.4% percent compared to the best IVst degrees, Beethoven's piano sonatas were using 1st degrees with 46.9% in intermediate section tone.